Social and Economic Conditions on Children's Education Level Fisherman Family in Nangadhero Village, Aesesa District Nagekeo District - Ledidiana Serang; Taufik Arifin; Murdjoli Rodja (Economic and Education Journal (Ecoducation), 2020)
Social and economic conditions of parents in the family which will affect the education received by children, seen from the level of parental education, parents' age, income, expenses and even environmental factors can also affect the level of education of a child. The research aims to find out how much influence social and economic conditions have on the level of education of children of fishermen families in Nangadhero village, Aesesa District, Nagekeo Regency, using the Ex-post facto method. The sample was 83 family heads from a total population of 105 families who work as fishermen. Data collection techniques using questionnaires and documentation, the results of research (1) There is a significant influence between social conditions on the level of education of fishermen children, with a tcount of 2.113> 1.667, and significant = 0.038 <0.05. (2) There is no significant influence between economic conditions on the education level of fishermen children, with a significant value> 0.05. (3) There is an influence of 10.2% between social conditions and economic conditions simultaneously on the educational level of children of fishermen families in Nangadhero village, Aesesa District, Nagekeo Regency.